PERSEPSI DAN MOTIVASI MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR (PGSD) TENTANG PROFESI GURU - Dyah Indraswati; Prihma Sinta Utami; Nursaptini .; Deni Sutisna; Setiani novitasari (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2020)
This study describes the perceptions and motivations students of Department of Primary Education concerning about the teaching profession along with the knowledge and experience they gained in college. The implications of the results of this study can provide a spectrum going forward so that Department of Primary Education study program managers can sustainably develop teacher professional programs to strengthen the identity of students as teacher candidates. This type of research is qualitative descriptive. The method used in this study is a survey method using an open questionnaire. The subjects of this study were 36 students of Department of Primary Education, Teacher Training and Education Faculty, Mataram University in the afternoon 7b class. The results showed all respondents stated that this profession is a noble profession, but they can switch to other jobs if income is more adequate. 83.33% of respondents said they were ready to become teachers while 16.67% said they were not ready to go into the field independently.